Social communication disorders among kindergarten children from the perspective of teachers in Sulaimani - Khalid, Prof.Dr.Hassan Fakhruddin; Ghafoor, Shakar Nazim (Sulaimani Journal for Humanities, 2026)
The aim of this study is to determine the level of social relationship disorders among kindergarten children from the perspective of teachers in Sulaimani according to the type of kindergarten (public, private) and according to the geographical location of education (east, west). Non-governmental organizations in Sulaimani for the academic year 2024-2025 that continue to work and the number of (1408) teachers, (156) male teachers and (1252) female teachers, the sample of the study (412) teachers of both sexes (male and female). The tool used was the scale of social communication disorders, which consisted of 36 items. The researcher used SPSS to analyze the data. 1. Social communication disorders among kindergarten children from the perspective of teachers in Sulaimani are at a high level. 2. The existence of statistically documented differences in the level of social interaction disorders among kindergarten children from the perspective of teachers according to the variable of kindergarten type (public, non-public) is a difference in favor of public kindergartens. 3. Lack of statistically documented differences in the level of social communication disorders among kindergarten children according to the variable of geographical location of education (East, West).
Keywords: Social communication disorders; kindergarten; kindergarten; social communication